1997
DOI: 10.1002/(sici)1096-8652(199707)55:4<193::aid-ajh5>3.3.co;2-y
|View full text |Cite
|
Sign up to set email alerts
|

Plasma tissue factor antigen levels in capillary whole blood and venous blood: Effect of tissue factor on prothrombin time

Abstract: To measure the amount of tissue factor released during specimen collection and its potential effect of shortening the prothrombin time, we measured tissue factor and pro-thrombin time in twenty-three paired venous and capillary blood samples from antico-agulated patients and in ten paired samples from controls. We also compared venous prothrombin time determined by a plasma-based assay with venous and capillary pro-thrombin time determined with a whole blood assay. Venous specimens were obtained using a two-sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…investigators. Plasma level of TF-Ag in healthy volunteers were within the range, observed by Quien et al (161 ± 42 pg/ml, mean ± SD) and Takahashi et al (138 ± 51pg/ml)[30,31]. Our finding for the mean plasma level of MP -TF activity 0.24 ± 0.12 pg /ml (mean ± SD) is in agreement with the findings of other studies, which have found that healthy individuals have very low levels of MP-TF activity[32,33].…”
supporting
confidence: 92%
“…investigators. Plasma level of TF-Ag in healthy volunteers were within the range, observed by Quien et al (161 ± 42 pg/ml, mean ± SD) and Takahashi et al (138 ± 51pg/ml)[30,31]. Our finding for the mean plasma level of MP -TF activity 0.24 ± 0.12 pg /ml (mean ± SD) is in agreement with the findings of other studies, which have found that healthy individuals have very low levels of MP-TF activity[32,33].…”
supporting
confidence: 92%
“…Venous blood was used for the Coagu-Chek PT system. Previous studies demonstrated good agreement between venous and capillary blood prothrombin times (8,9). There were systematic differences between the three lots of CoaguChek test strips and the IRPs (Table 1), but the mean differences were not greater than approximately 10%.…”
Section: Discussionmentioning
confidence: 63%